Agility and inter-organizational relations as elements of creating knowledge in an organization - Rzepka, Agnieszka; Olak, Andrzej (Archives of Business Research, 2017)
Knowledge and abilities of employees are the most important tools that serve the development of each organization. The dynamics of changes in modern economy requires from the people who manage an organization to have extremely high competences. This is dictated by an increasing competitiveness and constant pursuit to increase the value of the organization. The speed of changes that happen during this process is so big that it forces organization to make fast responses to emerging market opportunities. The use of such situations may direct the organization towards becoming an agile organization. Agility of an organization is one of the latest concepts which concerns both the organization itself as well as people employed in it. Therefore, the best solution is a process approach to creating and implementing organizational goals. One of the most important factors facilitating this process is the synergy of knowledge and possibilities of all organization's intangible resources. In this article the most important dependencies that condition the agility of an organization have been described.